Leader-Member Exchange in Educational Institutions - Hardianto Hardianto; Vivi Puspita Sari (STAI Hubbulwathan Duri, 2021)
This study is motivated by the lack of reading material related to Leader-Member Exchange (LMX) in educational institutions. LMX studies in Indonesia are more dominant incorporates. The purpose of this study was to determine the study of LMX in educational institutions in Indonesia. This research is library research, the primary source of which is articles from journals. The article was taken from google scholar and eric.go.id search engines with the keywords Leader-Member Exchange. Deductive and inductive methods carried out data analysis. The results showed that LMX influenced OCB, innovative work behavior, job satisfaction, organizational commitment, work engagement, employee voice, and performance. Increasing teacher LMX can be done by increasing self-efficacy and organizational justice.